Analysis of Icons, Indexes, and Symbols in YouTube Advertisement of SilverQueen Very Berry Yoghurt - Nabila, Risa; Nur Sakinah, R. Myrna (Journal of Scientific Research, Education, and Technology (JSRET), 2023)
Advertising as a material for semiotic study, this article describes the signs found in SilverQueen chocolate advertisements for the very berry yogurt flavor variant on YouTube and also the meaning of the signs between the signifier and signified based on the object. This study aims to find out signifiers and signifieds, find out the meaning contained in SilverQueen chocolate advertisements with very berry yogurt flavors on YouTube, such as how semiotics looks at the meaning of messages in advertisements. The method used in this study uses qualitative analysis methods. With this method, researchers can study and examine the meaning contained in a sign based on the information obtained by researchers, such as video footage in advertisements depicting messages for consumers, creating recognizable products with the intention of attracting consumer interest in the form of names, packaging, logo, price, and the power of image visualization.